2019
DOI: 10.1007/s00429-019-01909-6
|View full text |Cite
|
Sign up to set email alerts
|

Individual susceptibility to TMS affirms the precuneal role in meta-memory upon recollection

Abstract: Background: A recent virtual-lesion study using inhibitory repetitive transcranial magnetic stimulation (rTMS) confirmed the causal behavioral relevance of the precuneus in the evaluation of one's own memory performance (aka mnemonic metacognition).Objective: This study's goal is to elucidate how these TMS-induced neuromodulatory effects might relate to the neural correlates and be modulated by individual anatomical profiles in relation to meta-memory.Methods: In a within-subjects design, we assessed the impac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 54 publications
(64 reference statements)
3
38
0
Order By: Relevance
“…Intrinsic individual differences in functional connectivity between brain structures have informed our understanding of the varied ability to introspect about self-performance (Baird et al, 2013; Fleming et al, 2010; Ye et al, 2019). Here we found that resting-state functional connectivity of hippocampus and angular gyrus is specifically associated with vividness efficiency, while the connectivity of hippocampus and medial aPFC predicts metacognitive efficiency across individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Intrinsic individual differences in functional connectivity between brain structures have informed our understanding of the varied ability to introspect about self-performance (Baird et al, 2013; Fleming et al, 2010; Ye et al, 2019). Here we found that resting-state functional connectivity of hippocampus and angular gyrus is specifically associated with vividness efficiency, while the connectivity of hippocampus and medial aPFC predicts metacognitive efficiency across individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the IPL -DLPFC network makes use of the memory information from the precuneus for metacognitive decisions. Together with the precuneus -hippocampus connectivity (Ye et al, 2019), a cortico-hippocampal network of meta-mnemonic process is at work with primary mnemonic processes (McClelland et al, 1995;Wang et al, 2014;Zeidman et al, 2015), implicating the hippocampus in initiating the retrieval of the memory traces, which are then integrated to detailed recollections and conscious monitoring supported by the precuneus and the IPL (Richter et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies tapping into the OFC role in meta-related processes were all on perceptual decisions, such as odor discrimination judgment (Kepecs et al, 2008; Lak et al, 2014), whereas at present the tasks in question concern mnemonic decisions. Some recent work on humans has similarly evinced such specificity for perceptual versus memory related metacognition (Fleming et al, 2014; Ye et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%